2000
DOI: 10.1161/01.hyp.35.1.214
|View full text |Cite
|
Sign up to set email alerts
|

G-Protein β 3 Subunit Gene Variant and Left Ventricular Hypertrophy in Essential Hypertension

Abstract: Abstract-A functional genetic variant consisting of a C825T substitution in the GNB3 gene, encoding for the G-protein ␤ 3 subunit, has been associated with enhanced G-protein activation and cell growth. The aim of the study was to investigate the association of this polymorphism with left ventricular hypertrophy (LVH) in a sample of patients with essential hypertension. Left ventricular mass was assessed by 2-mode echocardiography in 86 patients with essential hypertension, and GNB3 C825T genotype was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 36 publications
3
47
1
1
Order By: Relevance
“…Interestingly, the relation was apparent in both parents and offspring analysed separately. This observation, in agreement with most of the studies evaluating the influence of the GNB3 on parameters of left ventricular function and structure, 8,10,11 has provided evidence for early onset and stability of this association over generations. Ageing is associated with alterations in functions of cardiac and vascular G-protein receptors with a potential to impair intracellular signalling and the ultimate cardiovascular phenotype.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Interestingly, the relation was apparent in both parents and offspring analysed separately. This observation, in agreement with most of the studies evaluating the influence of the GNB3 on parameters of left ventricular function and structure, 8,10,11 has provided evidence for early onset and stability of this association over generations. Ageing is associated with alterations in functions of cardiac and vascular G-protein receptors with a potential to impair intracellular signalling and the ultimate cardiovascular phenotype.…”
supporting
confidence: 90%
“…In addition, the early studies in Caucasian populations have demonstrated that a distribution of the C825T genotypes among subjects of European origin ensures appropriate epidemiological representation of each variant in population samples of different size. [6][7][8] …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…25 Two other reports involving hypertensive patients with and without left ventricular hypertrophy demonstrated a positive association between left ventricular mass and the 825T allele. 26,27 In contrast, a large population-based study did not reveal any association between cardiac structure and GNB3 T allele. 28 Association never proves causation.…”
Section: Discussionmentioning
confidence: 69%
“…In the samples from Israeli subjects, genotyping of the GNB3 C825T polymorphism was performed using polymerase chain reaction-restriction fragment length polymorphism [13] . In the samples from Spanish subjects, genotyping was performed using a newly-developed low-density DNA microarray based on allele-specifi c probes [6] .…”
Section: Genotypingmentioning
confidence: 99%